Chlorogenic acid: a review on its mechanisms of anti-inflammation, disease treatment, and related delivery systems - Huang, Jianhuan; Xie, Mingxiang; He, Liang; Song, Xiaoping; Cao, Tianze (Frontiers in Pharmacology, 2023)
Chlorogenic acid (CGA) is a bioactive compound ubiquitously present in the natural realm, lauded for its salient anti-inflammatory and antioxidant attributes. It executes its anti-inflammatory function by moderating the synthesis and secretion of inflammatory mediators, namely TNF-α, IL-1β, IL-6, IL-8, NO, and PGE2. Concurrently, it modulates key signaling pathways and associated factors, including NF-κB, MAPK, Nrf2, and others, bestowing protection upon cells and tissues against afflictions such as cardio-cerebrovascular and diabetes mellitus [1]. Nevertheless, the inherent low bioavailability of chlorogenic acid poses challenges in practical deployments. To surmount this limitation, sophisticated delivery systems, encompassing liposomes, micelles, and nanoparticles, have been devised, accentuating their stability, release mechanisms, and bioactivity [2]. Given its innate anti-inflammatory prowess and safety profile, chlorogenic acid stands as a promising contender for advanced biomedical investigations and translational clinical endeavors.